A bill to facilitate the decision of controversies at law, arising upon instruments under seal (House doc. (North Carolina. General Assembly. House of Commons), 1852)
1852 North Carolina House bill, report of the House Committee on the Judiciary, recommending that the bill not be passed, and an amendment to same. The subject of these actions concerned the procedure to be used to decide controversies arising from instruments under seals.